A Comparative Study on the Efficacy of Tramadol and Fentanyl Added To Low Dose Bupivacaine in Subarachnoid Block for Caesarean Section - Fazal Wadood, Madiha Zafar, Dur I Shahwar, Umar Iqbal, Shahid Adalat Chaudhry, Varda Balouch (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A caesarean section is the utmost communal surgical procedure. An adjuvant with a low dose of bupivacaine added to a cesarean section is a better option. Aim of the study: It is planned to study the effect of fentanyl and tramadol added to a low dose of bupivacaine on subarachnoid blockade in caesarean section. Place and duration: In the Anesthesia and Obstetrics and Gynecology department of Khyber Teaching Hospital, Peshawar and Arif Memorial Teaching Hospital, Lahore for six-moths duration from July 2021 to December 2021. Methods: 90 patients were randomized into three groups, 30 pregnant females in each group. Group A received 0.5% bupivacaine 7.5 mg (one and a half ml), 5% dextrose in 0.5 ml water and total of 2 ml, group B 0.5% bupivacaine 5 mg, fentanyl 50 µg, total 2 ml. In group C, 0.5% bupivacaine was used together with 50 mg of tramadol, and a total of 2 ml was used for spinal anesthesia. The height of the sensory block was evaluated by the method of pinprick and the quality of the motor block by the Bromage scale. The effective duration of analgesia was recorded when patients requested the 1st dose of analgesia. The APGAR score was documented at one and five minutes after the baby was born. Results: In group A; mean duration of blockade was 118.50 ± 23.60; It was 168.00 ± 30.21 mints in Group B and 215.00 ± 26.51 mints in C Group, which was significant between the three groups (P = 0.01). The systolic blood pressure has mean change among the three groups after 3, 4, 5, 6, 8, 9, 10, 20 and 30 min was significant after SAB, and the diastolic blood pressure mean change after SAB was significant at 2, 3, 8, 9, 10, 20 minutes and the p-value were 0.021, 0.037, 0.059, 0.032, 0.042, 0.065, respectively. Hypotension developed in 9 cases of A group; 10 patients of B Group and 6 in the C group. There was one case pruritus in group A; group B has 7 patients with itching and no group C has no case of itching. The measurement of VAS after SAB was significant between groups. There was also a significant variance in VLAS among the groups in the first hour (P = 0.00049), the 2nd hr. (P - 0.007), and the 3rd hr. (P = 0.001) after SAB, and the interaction between the groups was significant (P = 0.001). Conclusion: The combination of bupivacaine and tramadol may be a better option as an intrathecal anesthetic compared to 0.5% bupivacaine in 0.5 ml of 5% dextrose or 0.5% bupivacaine in combination with fentanyl. Keywords: SAB, Bupivacaine, Fentanyl and Tramadol